2009
DOI: 10.1681/asn.2008090957
|View full text |Cite
|
Sign up to set email alerts
|

The E-Selectin Ligand Basigin/CD147 Is Responsible for Neutrophil Recruitment in Renal Ischemia/Reperfusion

Abstract: E-selectin and its ligands are essential for extravasation of leukocytes in inflammation. Here, we report that basigin (Bsg)/CD147 is a ligand for E-selectin that promotes renal inflammation in ischemia/ reperfusion. The selectins and their ligands are essential for leukocyte tethering/rolling on endothelial cells and the initiation of inflammatory response. The selectins are C-type lectins and consist of three members, i.e., P-, L-, and E-selectin. 1,2 P-selectin is expressed upon inflammatory stimulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 50 publications
(49 reference statements)
6
91
0
Order By: Relevance
“…It is known that macrophages express Bsg, and that Bsg could be a ligand for E-selectin. 27,34 We also confirmed that Bsg on THP-1, the human monocytic cell line, bound to E-selectin (data not shown). Consider- ing that E-selectin expression was induced to similar degrees in both genotypes, it is likely that the difference in macrophage infiltration between Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice is due to the presence of Bsg on macrophages.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…It is known that macrophages express Bsg, and that Bsg could be a ligand for E-selectin. 27,34 We also confirmed that Bsg on THP-1, the human monocytic cell line, bound to E-selectin (data not shown). Consider- ing that E-selectin expression was induced to similar degrees in both genotypes, it is likely that the difference in macrophage infiltration between Bsg ϩ/ϩ and Bsg Ϫ/Ϫ mice is due to the presence of Bsg on macrophages.…”
Section: Discussionsupporting
confidence: 63%
“…44 However, little information about E-selectin is available. Because Bsg acts as an E-selectin ligand on inflammatory cells, 34 we next examined E-selectin expression in the kidney. We found that E-selectin expression was upregulated in the kidney after UUO surgery, but the expression levels were comparable between the genotypes ( Figure 2C).…”
Section: Macrophage Infiltration Is Lower In Bsg ϫ/ϫ Micementioning
confidence: 99%
See 1 more Smart Citation
“…The respiratory syncytial virus receptor, CX3CR1 (48,49), is found on intestinal macrophages, whereas CD81, an entry factor for hepatitis C virus, is also found on macrophages (50,51). Finally, it is evident from previous studies that Fc-FcγR-mediated cellular immunity plays a major role in mounting an effective protective response toward bacterial pathogens (52,53). Even in those circumstances, it is possible that a molecular bridge between the pathogen and the effector cell may enhance cell-mediated immunity.…”
Section: Discussionmentioning
confidence: 97%
“…Proteinaceous casts, tubular necrosis, and medullary congestion are established histologic features of ischemic AKI. 1,2,18,19 Histologic analyses revealed that Klf4 deletion significantly exacerbated the formation of proteinaceous casts and tubular necrosis and the degree of medullary congestion in response to I/R injury ( Figure 3). These results suggest that endothelial Klf4 plays a protective role in ischemic AKI.…”
Section: Endothelial Klf4 Deletion Exacerbated Renal I/r Injurymentioning
confidence: 99%